Pengaruh Electronic Word Of Mouth Dan Harga Terhadap Minat Beli Pakaian Bekas Pada Toko Online Thriftshop Berkah Mulia - Safriadi M Yunus Aks (Universitas 45 Surabaya, 2024)
Abstract This research aims to determine the influence of electronic word of mouth and price on interest in buying second-hand clothes. The sample used in this research was 97 respondents. Testing in this research used the Random Sampling Technique with the SPSS Version 25 Program. The data analysis methods used were regression analysis, multiple correlation, coefficient of determination, t test and f test. The results of hypothesis testing in this study (T test results) stated that electronic word of mouth had a significant effect on purchase interest. This can be seen from the t-value of 2.764 and the significance value of P-value 0.007, so the t-value is 2.764 < t-table df (97) = 1.975 (from the t table list) and the significance value is 0.007 > 0.05. So Ho is rejected and Ha is accepted, so these results show that Electronic Word of Mouth has a positive and significant effect on Purchase Interest. Price does not have a significant effect on Purchase Intention. This can be seen from the t-value of 0.041 and the significance value of the P-value of 0.000, so the t-value is 0.041 < t-table df(97) = 1.975 (from the t table list) and the significance value is 0.000 < 0.05. So Ho is accepted and Ha is rejected, so this result shows that price has no positive and insignificant effect on purchase interest. And the results of the Coefficient of Determination test show that the R Square value is 0.075, indicating that the independent variable (X) is able to explain 7.5% of the variation that occurs in the dependent variable (Y), while the remaining 92.5% is influenced by other factors that were not examined. in this research, for example product quality, social factors, lifestyle, brand image, etc.